2006
DOI: 10.1002/bit.20720
|View full text |Cite
|
Sign up to set email alerts
|

Reverting cholesterol auxotrophy of NS0 cells by altering epigenetic gene silencing

Abstract: NS0 is a cholesterol-requiring mouse myeloma cell line widely used in the production of recombinant antibodies. We have previously reported that the deficiency of 17beta-hydroxysteroid dehydrogenase type7 (Hsd17b7) is responsible for the cholesterol auxotrophy of NS0 cells. Here we demonstrate DNA methylation to be the mechanism underlying transcriptional suppression of Hsd17b7 in cholesterol dependent NS0 cells. Analysis of the DNA methylation pattern revealed methylation of the CpG-rich region upstream of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…conditions isn't negligible, it is clearly achievable (Birch et al, 1994;Kawamoto et al, 1983;Keen, 1995;Seth et al, 2006b). Consistent with the findings of these other groups, our results indicate that only a small percentage of NS0 cells are capable of growing in protein-free, cholesterol-free medium, as evidenced by the sharp decrease in viability that was seen in medium containing only 0.3% FBS.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…conditions isn't negligible, it is clearly achievable (Birch et al, 1994;Kawamoto et al, 1983;Keen, 1995;Seth et al, 2006b). Consistent with the findings of these other groups, our results indicate that only a small percentage of NS0 cells are capable of growing in protein-free, cholesterol-free medium, as evidenced by the sharp decrease in viability that was seen in medium containing only 0.3% FBS.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, it has been reported that cholesterol auxotrophy in NS0 cells is due to reduced expression of the Hsd17b7 gene, encoding a 3-ketosteroid reductase (Seth et al, 2006a). Methylation upstream of the Hsd17b7 gene appears to be responsible for transcriptional suppression of this gene (Seth et al, 2006b). However, the underlying mechanism of cholesterol prototrophy in the NS0-PFCF cells described here has not been characterized.…”
Section: Discussionmentioning
confidence: 97%
“…[10][11][12] NS0 cells lack endogenous glutamine synthetase (GS) enzyme activity making them suitable for use with GS as a selectable marker for recombinant antibody expression. 13 High antibody productivity has been reported from non-GS NS0 cell lines as well.…”
Section: Mammalian Expression Systemsmentioning
confidence: 99%
“…Two effects contribute: genomic variation between cell lines is observed [5], as well as what has been termed phenotypic drift: the slow but continuous changes and adaptations observed in cells maintained in culture for a prolonged period of time [15,16]. The latter can be caused by both genomic changes and epigenetic regulation [17][18][19]. This genomic and phenotypic heterogeneity has advantages and disadvantages: On the one hand it allows the effective selection of cells with different physiological and process relevant properties during screening [6,[20][21][22][23][24][25], on the other hand it limits the stability of these properties [21,26,27] and requires large numbers of subclones to be tested over prolonged periods of time to identify the few stable clones suited for production.…”
Section: Introductionmentioning
confidence: 99%